2016
DOI: 10.1016/j.wem.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Cycling Injuries in Southwest Colorado: A Comparison of Road vs Trail Riding Injury Patterns

Abstract: Lacerations and abrasions are the most common injuries sustained in cycling. Quantifying the role of protective extremity gear in reducing these injury patterns may be of interest for future studies. Protective helmet use may be important in reducing morbidity from cycling-related head trauma; however, more data are needed. Prehospital care providers responding to the injured trail cyclist should be equipped to manage laceration, fracture, head injury, and thoracic trauma in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 13 publications
0
32
0
1
Order By: Relevance
“…Only a few studies reported data on mortality during mountain biking [40,41,42]. In particular, Kim et al (2006) reviewed serious MTB injuries requiring trauma center admission during a 10 year study conducted in the three trauma centers of the Greater Vancouver area.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few studies reported data on mortality during mountain biking [40,41,42]. In particular, Kim et al (2006) reviewed serious MTB injuries requiring trauma center admission during a 10 year study conducted in the three trauma centers of the Greater Vancouver area.…”
Section: Resultsmentioning
confidence: 99%
“…This conception, however, may be wrong. It has been reported that road-biking is more often associated with head-trauma, whereas off road cycling causes a greater number of less severe injuries [11].…”
Section: Discussionmentioning
confidence: 99%
“…In total, 367 sources were identified from the following recreational pursuits: climbing (21), mountain biking (22), scooters (19), skateboarding (21), skating (22), equestrian (47), hang-gliding and paragliding (30), skydiving (16), BASE jumping (9), surfing (32), wind and kitesurfing (16), white-water kayaking and rafting (11), downhill skiing (33), cross-country skiing (11), snowboarding (40), sledding (14) and curling (3).…”
Section: Methodsmentioning
confidence: 99%
“…While head and neck injuries are more common among road (16%) vs. mountain bike (off-road) riders (6%) [30], mountain bikers experience considerable head acceleration during the pursuit of their activity [31] While helmets will lower the impact of an injury [32], they do not entirely prevent head them [33,34]. Comparisons of the incidence of head and neck injuries between amateur and the professional and elite level of the sport have shown inconsistent results [35,36].…”
Section: Mountain and Trail Bikingmentioning
confidence: 99%